Friends. The complete third season [videorecording (DVD)] - Mancuso, Gail, 1958-; Bright, Kevin, 1955-; Aniston, Jennifer; Cox, Courteney, 1964-; Kudrow, Lisa (Warner Bros. Entertainment, 2010)
Follows the lives of six friends living in New York.